Violence Against Women in Politics. - Krook, Mona Lena (Oxford University Press USA - OSO, 2020)
This book provides the first comprehensive account of violence against women in politics. Tracing its emergence as a concept, Mona Lena Krook draws on research in multiple disciplines to theorize that this phenomenon is not simply a gendered extension of existing definitions of political violence privileging physical aggressions against rivals. Rather, it is a distinct phenomenon involving a broad range of harms to undermine women as political actors. Adopting a global comparative approach, Krook illustrates what this violence looks like in practice and catalogues emerging solutions around the.